Children’s Involvement in Environmental Management Programs to Alleviate Post-Disaster Trauma in West Suli, Luwu Regency - Nurdin Kaso; Andi Arif Pamessangi; Muhammad Zuljalal Al Hamdany; Ervi Rahmadani; Muhammad Faiz; Munalir (LP2M of Institute for Research and Community Services - UIN Walisongo, 2026)
This community service program aims to engage children in environmental management activities as a strategy for post-disaster trauma recovery in West Suli. The activities were designed to provide space for emotional expression and psychosocial recovery through educational, recreational, and participatory initiatives, such as environmental education programs, tree planting, and environmental clean-up activities. The implementation method involved a participatory approach using Asset-Based Community Development, facilitated by the community service team. The main subjects of this program were 18 children in Salubua Village. Data collection techniques included observation, interviews, questionnaires, and documentation. The results indicate that the active involvement of children in the program not only increased their awareness and concern for the environment but also helped reduce anxiety and improve their spirit of life after the disaster. It is expected that this program can serve as a model for community-based recovery that sustainably integrates environmental aspects with children's mental health.